Phytoremediation of heavy metals by the dominant mangrove associate species of Indian Sundarbans - Mukherjee, Pritam; Pramanick, Prosenjit; Zaman, Sufia; Mitra, Abhijit (Journal of Environmental Engineering and Landscape Management, 2021)
The present study aims to investigate the phytoremediation potential of zinc (Zn), copper (Cu), and lead (Pb) by two dominant mangrove associate species, Suaeda maritima, and Salicornia brachiata, found in the high saline supralittoral zone of Indian Sundarbans in four stations of the Hooghly-Matla estuarine complex during the premonsoon season (May 2019). We found that concentrations of biologically available heavy metals (HMs) in the ambient soil and bioaccumulated HMs within the vegetative plant parts occurred as per the order: Sagar South > Bakkhali > Jharkhali > Bali Island. The order of biologically available and bioaccumulated HMs was Zn > Cu > Pb. Interestingly, the selected HMs display high organ-specificity for both species with the highest enrichment in roots, followed by stems and leaves. We propose that these halophytes could be used as agents of phytoremediation and their farming would be effective in the ecorestoration of this deltaic complex in context to conservative pollutants.